Map of Export Product Competition of Indonesia, Malaysia, Singapore, and Thailand - Jayadi, Akhmad; Aziz, Harry Azhar (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2016)
This research attempts to investigate the export product competitiveness of Indonesia, Malaysia, Singapore, and Thailand which are classified into five major groups: primer product, natural research-intensive product, unskilled labor-intensive product, technology-intensive product, and human capital-intensive product. The method used in this research is product mapping, which is the combination between Revealed Symmetric Comparative Advantage (RSCA) and Trade Balance Index (TBI). The result shows that Indonesia has a comparative advantage in the export specialization of primary products, natural research-intensive products, and unskilled labor-intensive products. Singapore and Malaysia have a comparative advantage in technology-intensive products, while Thailand has a human capital-intensive product. This research proves the flying geese pattern of the five groups of products, that if a country becomes a leader of one product, it will become a follower in another product.